2018
DOI: 10.1038/s41591-018-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

Resetting the epigenetic balance of Polycomb and COMPASS function at enhancers for cancer therapy

Abstract: MLL3 (also named KMT2C) is a COMPASS subunit that implements H3K4 mono-methylation at gene enhancers. KMT2C frequently incurs point-mutations across a range of human tumors, nevertheless precisely how these lesions alter MLL3 function and contribute to oncogenesis is unclear. Here we report a cancer mutational hotspot in MLL3 within its Plant Homeo Domain (PHD) repeats and demonstrate that this domain mediates association with the histone H2A deubiquitinase and tumor suppressor BAP1. Cancer-associated MLL3 PHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 59 publications
(66 reference statements)
11
140
4
Order By: Relevance
“…Promoter region immunoprecipitation either as direct binding or through long-range enhancer interactions has previously been reported for both KMT2C and KMT2D [36,37]. KMT2C binding upon the promoter region of the ATM, ATR, BRCA1, and BRCA2 genes is independently corroborated in a recently published analysis [38] (Appendix Fig S3). Interestingly in the same study, a 32% of KMT2C is located within promoter regions, indicating roles for KMT2C besides enhancer H3K4 monomethylation.…”
Section: Kmt2c Localizes At Promoters and Controls The Expression Of supporting
confidence: 55%
“…Promoter region immunoprecipitation either as direct binding or through long-range enhancer interactions has previously been reported for both KMT2C and KMT2D [36,37]. KMT2C binding upon the promoter region of the ATM, ATR, BRCA1, and BRCA2 genes is independently corroborated in a recently published analysis [38] (Appendix Fig S3). Interestingly in the same study, a 32% of KMT2C is located within promoter regions, indicating roles for KMT2C besides enhancer H3K4 monomethylation.…”
Section: Kmt2c Localizes At Promoters and Controls The Expression Of supporting
confidence: 55%
“…Nevertheless, this study provides the most comprehensive description, to date, of the molecular events that characterise the progression of malignancy in SPN and indicates alterations of BAP1 and KDM6A as potential drivers of metastasis in SPNs. This might have important therapeutic implication as, in other tumour types, BAP1 loss and reduced expression of KDM6A have been shown to drive malignancy through epigenetic alterations that can be pharmacologically reverted . Although we have provided evidence that mechanisms can be shared between different malignancies, it remains to be determined whether BAP1 and KDM6A alterations are promoting tumour growth in SPNs through a similar epigenetic mechanism.…”
Section: Discussionmentioning
confidence: 91%
“…Mutations of BAP1 and KDM6A were concurrent in the primary and one metastatic lesion of case SPN13, and co‐occurring mutations of these genes have already been reported in bladder cancer . KDM6A (also known as UTX) is a core component of the ‘complex of proteins associated with SET1’ (COMPASS) and it has been shown to require BAP1 for its recruitment at chromatin enhancers . Inactivation of those genes has been reported to occur through different mechanisms, ranging from DNA methylation to complex DNA rearrangements , which can be missed by targeted DNA sequencing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will likely involve differential recruitment of possibly uncharacterized cofactors. Of note, a recent study has shown that mutations in the PHD domain of a close paralog of KMT2D, the methyltransferase KMT2C, disrupt the interaction with a previously unknown cofactor, BAP1, reducing the recruitment of KMT2C to gene enhancers (Wang et al, 2018). Similar studies in combination with cryo-electron microscopy studies of full-length KMT2D will provide important structural and functional insights of the regulatory mechanism(s) of this posttranslational modification.…”
Section: Discussionmentioning
confidence: 99%